A study on the efficiency of propyl paraben as a preservative in dehydrated candied papaya - Yang, Amelia G.
The preservative effect of propyl paraben in dehydrated candied papaya was determined by evaluating its activity against the spoilage microorganisms of the product. In Phase I, the spoilage microorganisms were isolated from spoiled sample and were used as the inoculum in the second phase. The isolates consisted of two species of bacteria and two species of molds. In the second phase, thew effectivity of paraben was compared with that sodium benzoate at 0.02% and 0.05% concentrations and at pH 4.5, pH 6, and pH 8. The results showed that paraben was effective at all pH tested at 0.05% concentration. Sodium benzoate was found effective t pH 4.5 at 0.02% and 0.05% concentrations. In the third phase, microbiological and sensory qualities of the paraben treated samples were evaluated. The results showed that paraben treated samples were more stable and remained unspoiled up to six weeks of storage. Sensory evaluation showed that samples treated with either preservative did not have any significant difference at 5% level of significance. The paraben treated sample was the most preferred in terms of color, texture, flavor, and general acceptability.